Explanation of Increase of People’s Welfare through National Craftsmanship in Historical, Scientific and Literary Sources - Meliboeva Sarvinoz Sobirjon kizi (International Journal on Integrated Education, 2022)
This article is devoted to the historical, scientific and literary sources of improving the well-being of the people by means of national handicrafts. It also provides an analytical statement of the role of national handicrafts in social life, its importance and the opinions of Eastern thinkers about it.